(untitled) (Swiss Medical Weekly, 2020)
AIMS OF THE STUDY The Cancer Registry Zurich, Zug, Schaffhausen and Schwyz is one of the oldest cancer registries in Switzerland, first registering tumours in 1980 for the canton of Zurich. The aim of this study was to analyse trends in incidence and mortality for the most common types of cancer in the canton of Zurich from 1981 to 2017. METHODS In this analysis of population-based cancer registry data, we included malignant tumours of the breast (ICD10 C50), prostate (C61), colon/rectum (C18–C21), lung (C33–C34), and melanoma (C43), diagnosed between 1981 and 2017. Age-standardised incidence and mortality rates per 100,000 person-years were computed using the 1976 European Standard Population. Incidence and mortality time trends were assessed using joinpoint regression analysis. RESULTS In men, incidence for prostate cancer and melanoma increased over the study period, while it decreased for colon/rectum and lung cancer. A joinpoint for prostate cancer indicated the start of a decreasing trend in 2002. In women, incidence increased for breast cancer, lung cancer and melanoma; no trend was observed for colon/rectum cancer. Cancer mortality decreased for prostate, colon/rectum and lung cancer in men, with no clear trend for melanoma. In women, mortality decreased for breast cancer, colon/rectum cancer and melanoma, but increased for lung cancer. CONCLUSIONS The overall increasing incidence trends for prostate and breast cancer, as well as for melanoma, are in line with data from other Western countries. While lung cancer incidence is decreasing in men, it is still on the rise in women. Despite increasing incidence rates, mortality rates are decreasing for all localisations except for lung cancer in women. The opposite direction of incidence and mortality curves is probably mostly due to better and more effective treatment options, as well as earlier detection.